Supporting argumentation in mathematics classrooms - John Francisco (LUMAT, 2022)
Reform movements in mathematics education advocate that mathematical argumentation play a central role in all classrooms. However, research shows that mathematics teachers at all grade level find it challenging to support argumentation in mathematics classrooms. This study examines the role of teachers’ mathematical knowledge in teachers’ support of argumentation in mathematics classroom. The study addresses a documented need for a better understanding of the relationship between mathematical knowledge for teaching and instruction by focusing on how the knowledge influences teachers’ support of argumentation. The results provide insights into particular aspects of teachers’ mathematical knowledge that influence teachers’ support of students’ development of valid mathematical arguments in mathematics classrooms and suggest implications for research and practice.